Source of Chronic Inflammation in Aging - Sanada, Fumihiro; Taniyama, Yoshiaki; Muratsu, Jun; Otsu, Rei; Shimizu, Hideo; Rakugi, Hiromi; Morishita, Ryuichi (Frontiers in Cardiovascular Medicine, 2018)
Aging is a complex process that results from a combination of environmental, genetic, and epigenetic factors. A chronic pro-inflammatory status is a pervasive feature of aging. This chronic low-grade inflammation occurring in the absence of overt infection has been defined as “inflammaging” and represents a significant risk factor for morbidity and mortality in the elderly. The low-grade inflammation persists even after reversing pro-inflammatory stimuli such as LDL cholesterol and the renin–angiotensin system (RAS). Recently, several possible sources of chronic low-grade inflammation observed during aging and age-related diseases have been proposed. Cell senescence and dysregulation of innate immunity is one such mechanism by which persistent prolonged inflammation occurs even after the initial stimulus has been removed. Additionally, the coagulation factor that activates inflammatory signaling beyond its role in the coagulation system has been identified. This signal could be a new source of chronic inflammation and cell senescence. Here, we summarized the factors and cellular pathways/processes that are known to regulate low-grade persistent inflammation in aging and age-related disease.